Pengaruh Penerapan Latihan Bola Di Gantung Terhadap Kemampuan Service Atas Pemain Bolavoli Putra - Annisa Noviandri Dwi Putri; Muhamad Sazeli Rifki; Donal Syafrianto (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
Writing this journal aims to determine the effect of hanging ball training on the ability of top service in volleyball games. The problem in this study is the low service ability of male volleyball players at SMA Negeri 1 Luhak Nan Duo, West Pasaman Regency. The purpose of this study was to determine the influence of the application of hanging ball training on the service ability of male volleyball players at SMA Negeri 1 Luhak Nan Duo, West Pasaman Regency. This type of research is quasy experimental research (quasy experiment). This research was carried out in the month of February-April 2021 which was carried out in the volleyball field of SMA Negeri 1 Luhak Nan Duo, West Pasaman Regency. The population in this study were 18 people. The sampling technique used purposive sampling, so the number of samples in this study was 10 people. The research instrument is the top service test. The data analysis technique used t test analysis. The results of this study are the application of hanging ball training has an effect on the service ability of male volleyball players at SMA Negeri 1 Luhak Nan Duo, West Pasaman Regency. Tcount> ttable (4.08> 1.83). Where from the average service ability of 30.2 points, it increased to 37.2 points (increased by 6.9 points).